2021
DOI: 10.1186/s12889-021-10211-2
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practice in China from 2013 to 2018: a study from a national dynamic follow-up surveillance

Abstract: Background Breastfeeding is important for the physical and psychological health of the mother and child. Basic data on breastfeeding practice in China are out-of-date and vary widely. This study aimed to evaluate the progress of breastfeeding practice in China, as well as to explore the bottlenecks in driving better practice. Methods This was an observational study. We used data from the Under-5 Child Nutrition and Health Surveillance System in Chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Second, the breastfeeding rate in our study is quite high (48.8%), and one of the explanations for this is that our data were mostly collected in relatively developed areas with better breastfeeding practices and related services in local maternal and child health hospitals. During the study period, the Chinese government implemented national initiatives to promote breastfeeding practices by releasing breastfeeding-related systems [ 55 ]. Diverse types of evaluations, management, and supervision were used to build a friendly environment for breastfeeding, and hospitals were evaluated by the government for their baby-friendly status.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the breastfeeding rate in our study is quite high (48.8%), and one of the explanations for this is that our data were mostly collected in relatively developed areas with better breastfeeding practices and related services in local maternal and child health hospitals. During the study period, the Chinese government implemented national initiatives to promote breastfeeding practices by releasing breastfeeding-related systems [ 55 ]. Diverse types of evaluations, management, and supervision were used to build a friendly environment for breastfeeding, and hospitals were evaluated by the government for their baby-friendly status.…”
Section: Discussionmentioning
confidence: 99%
“…In China, as estimated by a nationally representative survey in 2013, 20.7% of infants under 6 months were exclusively breastfed according to the reported diets during the 24 h [ 7 ]. The Under-5 Child Nutrition and Health Surveillance System shows that the prevalence of exclusive breastfeeding measured by diet recall of the previous 24 h increased from 16.14% in 2013 to 34.90% in 2018 in China, with an annual percent of change of 14.90% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the rates of exclusive breastfeeding during the first six months in 2008 and 2018 were below the WHO’s target of 50% towards 2025 [ 22 ], and the prevalence of early initiation of breastfeeding was among the ‘poor’ levels according to the WHO standard (poor: <= 29%, medium: 30–49%, good: 50–89%, excellent: >= 90%) [ 23 ]. In comparison with the Chinese national data of U5CNHSS (34.9%) [ 8 ] and regional data of Nanning (37%) [ 11 ] in 2018, exclusive breastfeeding in Northeast China in 2018 (47.6%) was higher. Our result was consistent with the U5CNHSS finding that the prevalence of exclusive breastfeeding was higher in the east (39.3%) than in the west (25.7%) [ 8 ].…”
Section: Discussionmentioning
confidence: 82%
“…For example, a population-based survey (n = 10,408) conducted in 12 provinces / municipalities in 2017–18 reported that less than 10% of children received early initiation of breastfeeding, and no more than 30% were exclusively breastfed within six months [ 6 , 7 ]. Data from the Under-5 Child Nutrition and Health Surveillance System (U5CNHSS) demonstrated slightly higher coverage, with higher prevalence of exclusive breastfeeding (According to the WHO definition, “exclusive breastfeeding” was taken to mean feeding of infants 0–5 months old with breast milk but neither liquid foods nor solid / semi-solid / soft food during the previous 24 h) observed in the East (39.3%) than the West (25.7%) [ 8 ]; however, the rates still lagged behind the global average. The prevalence and determinants of breastfeeding vary widely across geographical regions in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation